Epilepsy Case Studies Pearls for Patient Care - Tatum, William O.; Sirven, Joseph I.; Cascino, Gregory D. (Springer International Publishing : Imprint: Springer, 2014)
Written by expert epilepsy clinicians from the Mayo Clinic, Epilepsy Case Studies: Pearls for Patient Care presents a wide variety of case histories drawn from "real life" experiences in people with seizures. Designed to stimulate the same deductive reasoning that is commonly used when seeing epilepsy patients in the clinic, this practical book presents the clinical scenario and then poses a range of stimulating questions to organize the reader's thoughts to address each case. Questions that revolve around each case include common ones such as "How does this test help us with the diagnosis?" and "What is the precise relationship of the patient's seizures to their overall neurological condition?" The most poignant questions include "How does this information help us to devise a treatment plan?" and "What do we know about the anticipated course and prognosis?" The questions raised in each section incorporate the clinical course and evaluation. Where possible, the discussion relies upon the latest medical evidence to support the responses and includes up-to-date techniques used for patients with and without seizure control. At the end of each case a few salient citations are referenced, as are a few of the more pertinent articles that the reader can reference to obtain an overview of the topic. Take-home messages are encapsulated in the form of clinical pearls that are designed to form the basic understanding of the case scenarios presented. A major contribution to the literature in epileptology, Epilepsy Case Studies: Pearls for Patient Care will be an invaluable reference for all clinicians who treat patients with epilepsy.